Kecenderungan bertindak curang pada isteri yang suaminya bekerja di luar bandar ditinjau daripada faktor kesepian dan keperluan afiliasi - Yohan Kurniawan,; Henny Yulianti,; Jaka Santosa Sugadijono, (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2010)
Act dishonestly or in Indonesia called the "cheating", either with or without sexual contact occurred in many communities during this. The act of cheating in a marriage can be done by both men and women. This study aimed to identify what factors influence the loneliness and affiliation needs of fraudulent behavior on the wife of her husband worked in the rural areas. The study was conducted using a survey questionnaire form. Number of subjects involved in this study a total of 35 respondents. Data analysis techniques were used frequency distribution and linear regression analysis. The results of this study indicate that there is a feeling the effects of the factors that tend to silence the unfaithful wife whose husband works in the rural areas. The relationship between factors feeling lonely with the tendency to cheat is positive, this means that the stronger the feeling of silence that felt someone, the more powerful is the tendency to do dishonest behavior. The study also shows that there is a positive influence between the loneliness feeling and the need of affiliation with the tendency to cheat, the more it needs lead to increasingly stronger affiliation tendency to cheat (R =0,722). Although both factors contributed significantly to the existence of fraudulent behavior on the wife of her husband worked in the rural areas, but the factors affecting the feeling of silence more powerful than the fact that the need to establish close relationships with others